Syringoma. Why is it so difficult for a dermatologist to make a clinical diagnosis? - Larisa I. Glebova; Ekaterina V. Zadionchenko; Ekaterina E. Radionova; Yulia A. Murashova (LLC "MEDIAFORMAT", 2023)
Syringoma is a fairly rare benign neoplasm of the dermal appendages of the sweat glands. Basically, rashes are typical for middle-aged women. Linear and eruptive skin rashes have been described. The article traces the anamnesis of the disease in a woman who for a long time in different cities of Russia could not be correctly put diagnose.